Stylistic Construction of Nationalism and Colonial Resistance in Chairil Anwar’s Poetry - Rarajelita Rarajelita; Rosmawaty Harahap (Winaya Inspirasi Nusantara Foundation, 2026)
Literary works produced during colonial periods often function as sites where language, ideology, and resistance intersect. In Indonesian literary history, the poetry of Chairil Anwar occupies a central position in articulating nationalist consciousness during the late colonial era. While existing scholarship has extensively discussed the thematic dimensions of Anwar’s poetry, comparatively limited attention has been given to how linguistic form itself contributes to the construction of resistance and nationalism. Addressing this gap, the present study aims to examine how stylistic features in Chairil Anwar’s patriotic poetry linguistically represent colonial resistance and national identity. The study adopts a qualitative stylistic research design. Data consists of selected patriotic poems by Chairil Anwar sourced from authoritative published collections. Using a stylistic framework informed by established models in literary linguistics, the analysis focuses on lexical choice, figurative language, and syntactic structure. Data were analyzed through systematic identification, close interpretation, and contextualization of linguistically salient features within the sociohistorical context of colonial Indonesia. The findings reveal that nationalism and resistance are constructed through dense resistance-oriented lexicon, symbolic imagery grounded in collective experience, and syntactic patterns emphasizing agency, urgency, and unity. These stylistic strategies work cohesively to embed ideological meaning within poetic form rather than presenting it explicitly. The study demonstrates that language functions as an active ideological resource in Anwar’s poetry. This research contributes to Indonesian literary studies by providing a linguistically grounded analysis of nationalist poetry and highlights the value of stylistics for examining non-Anglophone literary traditions within postcolonial scholarship.